THE IMPORTANCE OF PLAY IN EARLY CHILDHOOD EDUCATION AND ITS BENEFITS IN THE TEACHING-LEARNING PROCESS - Alves Marinho, Eliege (Revista Gênero e Interdisciplinaridade, 2024)
In Brazil, playfulness was implemented in Early Childhood Education as a tool to support teaching after the introduction of Escola Nova, recognizing playing as a component of childhood and human development. Through playfulness in Early Childhood Education it is possible to work on the development of the field of affective, emotional, intellectual, physical and social growth, stimulating activities that focus on the intellectual and emotional development of children. The objective of this study is to build a literature review on the importance of play in the teaching-learning process in Early Childhood Education, discussing its benefits during the educational process. The present study is a bibliographical study, an integrative literature review. Articles published between 2018 and 2023, in Portuguese and English, available in full text, were included. Secondary source data from the public domain was used, that is, the research does not pose any risk, therefore, there was no need to submit it to the Ethics Committee. After careful analysis of the available literature, 07 articles were selected to compose this study. It was observed that the authors argue that it is in childhood that children have a naturally playful interpretation of the world, perceive this demand and develop auxiliary teaching strategies that contribute to the teaching-learning process. In the early years, children tend to learn intuitively, where play can be used in the most different curricular subjects to enhance the teaching-learning process. Thus, this teaching strategy has proven to be successful, as it enables the development of skills that enhance the learning process such as perception, memorization, attention and sensation. In this way, it can be concluded that play is an important strategy for developing education in a dynamic, attractive and effective way. Its numerous benefits in the teaching-learning process highlight the importance of its inclusion in the school space.